Identification Of Freshness Level Of Mackerel (Rastrelliger Kanagurta) In Tanjungsari Market, Sumedang Regency. - Junianto, Junianto; Muhikun, Bahrun; Sigar, Yosia Petersen; Hanifa, Faiza; Putra, M Zidan; kusumah, Tiranti damayanti (Indonesian Journal of Aquaculture Medium, 2025)
Fresh fish or wet fish is fish that has not been or is not preserved with anything except simply cooled with ice. Fish is said to have maximum freshness if its properties are still the same as live fish, both in appearance, taste, and texture. The level of freshness of fish can be identified or assessed organoleptically. Human senses are instruments used in Volume 5, Number 2, June 2025 https://journal.unram.ac.id/index.php/jmai/index. E-ISSN : 2798-0553 31 organoleptic tests, which include sight, smell, taste, touch and hearing. This study aims to determine the level of freshness of mackerel and fresh fish at Tanjung Sari Market organoleptically. This research method is by taking mackerel samples and at 10.00 WIB, then its freshness is identified qualitatively through organoleptic observations. Sampling was carried out on May 20, 2025. Organoleptic assessment is the most widely used method in determining signs of fish freshness because it is easier and faster to do, does not require a lot of equipment, and does not require a laboratory. Subjective (organoleptic) determination of fish quality decline is carried out using a score sheet that has been set by the National Standardization Agency SNI 01-2346-2006 (BSN 2006) and using 5 (five) panelists. The parameters observed are the condition of the eyes, gills, mucus, meat, odor, and texture. For organoleptic observations, a detailed assessment (see the score sheet table) is carried out on the fish in the range of values 1 to 9. In the organoleptic testing of test fish sold in retail by traders at Tanjungsari market, the values obtained ranged from 7-8, which means that the fish still has good quality and meets the requirements set by SNI (2006), namely the standard for fresh fish for organoleptic testing, which is a minimum of 7.